INTERNALISASI PENDIDIKAN EKONOMI KELUARGA DALAM MENANAMKAN JIWA WIRAUSAHA ANAK (STUDI KASUS KELUARGA PETERNAK AYAM DI DESA PONGGOK) - Muhammad ari kusuma; Lisa Rokhmani (Jurnal Pendidikan Ekonomi, 2019)
This study aims to analyze how the internalization of economic education carried out in the family of chicken farmers in the Ponggok Village in order to instill entrepreneurial spirit to children. The approach in this research uses a qualitative descriptive approach to the type of case study research. The subject of this research was the chicken breeder of Ponggok Village which was selected through the Purposive Sampling technique. The results of this study indicate that the process of internalizing the Economic education of Ponggok village chicken farm families consists of exemplary, verbal explanations, habituation, and discussion of relevant cases.